Decisions on cancer care by Indigenous peoples in Alberta and Saskatchewan: a narrative analysis - Rose Roberts; Gary Groot; Tracey Carr (Rural and Remote Health, 2020)
Introduction: The prevalence of cancer is increasing among Indigenous peoples in Canada. To enhance quality of life of those Indigenous people affected by cancer, their decision-making experiences must be understood. This article presents the findings of a qualitative study exploring the treatment decision-making practices among Indigenous peoples with cancer in rural and remote Alberta and Saskatchewan, Canada. Methods: This study employed a qualitative narrative-based approach using the Indigenous research method of storytelling. Seventeen Indigenous participants (14 women, three men) with various forms of cancer were interviewed. Open-ended questions were used that were designed to understand participants' decision-making processing regarding their cancer treatment. Results: Keeping with Indigenous methodology, the interview transcripts were analysed by a narrative method, with the intent that the data would be presented in story format. Eight vignettes relating to decision making were created: being strong for family; family support; strength and independence; denial and not wanting to know; fear-based decision making; finding the blessing; the spiritual journey; and traditional medicine and doctors. Participants were involved in validating the analysis to ensure that data were accurately interpreted. Conclusion: The vignettes demonstrate the similarities and differences among Indigenous people with cancer from other countries. A primary feature is that family members play a central role in participants' cancer treatment decisions. While some participants embraced and relied upon traditional medicines, others were supported by the providers of Western health care. A healthcare system that provides access to both traditional and Western medicine can be essential to culturally safe, high-quality cancer care for Indigenous peoples.